Scalable fabrication of size-controlled chitosan nanoparticles for oral delivery of insulin. (June 2017) - He, Zhiyu; Santos, Jose Luis; Tian, Houkuan; Huang, Huahua; Hu, Yizong; Liu, Lixin; Leong, Kam W.; Chen, Yongming; Mao, Hai-Quan
Abstract: Controlled delivery of protein would find diverse therapeutic applications. Formulation of protein nanoparticles by polyelectrolyte complexation between the protein and a natural polymer such as chitosan (CS) is a popular approach. However, the current method of batch-mode mixing faces significant challenges in scaling up while maintaining size control, high uniformity, and high encapsulation efficiency. Here we report a new method, termed flash nanocomplexation (FNC), to fabricate insulin nanoparticles by infusing aqueous solutions of CS, tripolyphosphate (TPP), and insulin under rapid mixing condition ( Re  > 1600) in a multi-inlet vortex mixer. In comparison with the bulk-mixing method, the optimized FNC process produces CS/TPP/insulin nanoparticles with a smaller size (down to 45 nm) and narrower size distribution, higher encapsulation efficiency (up to 90%), and pH-dependent nanoparticle dissolution and insulin release. The CS/TPP/insulin nanoparticles can be lyophilized and reconstituted without loss of activity, and produced at a throughput of 5.1 g h −1 when a flow rate of 50 mL min −1 is used. Evaluated in a Type I diabetes rat model, the smaller nanoparticles (45 nm and 115 nm) control the blood glucose level through oral administration more effectively than the larger particles (240 nm). This efficient, reproducible and continuous FNC technique is amenable to scale-up in order to address the critical barrier of manufacturing for the translation of protein nanoparticles.